Acute torsion and ischemia of the appendix in a young child - Dhruvin H. Hirpara; Georges Azzie (Elsevier, 2018)
Torsion of the vermiform appendix is a rare diagnosis; its clinical and radiographic presentation can mimic that of acute appendicitis. We report the case of a two-year-old boy presenting with a one day history of lower abdominal pain and serial ultrasound examinations suspicious for atypical acute appendicitis. Operative findings revealed a necrotic and engorged appendix with a 720° clockwise torsion at its base. Final pathology was consistent with ischemic necrosis in the setting of lymphoid hyperplasia. A brief update on the current body of literature regarding pediatric torsion of the vermiform appendix is provided. Keywords: Appendicitis, Volvulus, Torsion